Batasan Pertanggungjawaban Korporasi atas Kebakaran Lahan Skala Besar - Ali, Muh. Ansar; Sumantri , Sumantri; Asnur, Vani Fadillah; Raharja, Rachmad Giri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Large-scale land fires in Indonesia have multidimensional impacts on the environment, public health, and national economic losses. In practice, corporate involvement in land clearing and management is often linked to forest and land fires, raising issues regarding the limits of corporate legal liability. This study aims to analyze the forms and limits of corporate liability for large-scale land fires based on positive law provisions in Indonesia. The research problem formulation includes how corporate liability is regulated in land fire cases and the factors that limit the application of such liability. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that corporations can be held criminally, civilly, and administratively liable if proven negligent or intentional in causing land fires. However, the application of this liability still faces obstacles such as proving causal relationships, weak oversight, and the complexity of corporate structures. In conclusion, strengthening regulations and more effective law enforcement are needed so that corporate liability can be optimally implemented to prevent the recurrence of large-scale land fires